Updated ACR guidelines for the management of axial spondylitis - Sh. Erdes (Научно-практическая ревматология, 2020)
The paper provides the updated American College of Rheumatology (ACR) guidelines for the treatment of ankylosing spondylitis and non-radiographic axial spondyloarthritis.